Organizational Climate and Work Motivation On Organizational Commitment: The Mediating Role of Job Satisfaction - Ramaditha, Shava; Susilo, Heru; Riza, Muhammad Faisal (Graduate School Universitas Brawijaya, 2026)
Objective: This study examines the influence of organizational climate and work motivation on organizational commitment, with job satisfaction acting as a mediating variable. Organizational commitment plays an important role in maintaining employee loyalty and productivity, especially in competitive work environments where companies face increasing employee turnover, communication challenges between leaders and employees, unclear job responsibilities, and dissatisfaction with existing work systems. These issues may reduce job satisfaction and weaken employees’ commitment to the organization. Therefore, this study aims to analyze the relationships among organizational climate, work motivation, job satisfaction, and organizational commitment in order to identify strategies to improve employee loyalty and performance. Design/Methods/Approach: This research employs a quantitative approach, using questionnaire data collected via Google Forms from 68 employees of PT Telekomunikasi Seluler Tbk. in the Malang Raya area, East Java, selected purposively. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3 Findings: The findings indicate that organizational climate and work motivation have significant effects on job satisfaction; job satisfaction significantly influences organizational commitment; and both organizational climate and work motivation also directly affect organizational commitment; however, their effects are stronger when mediated by job satisfaction. These results highlight the importance of creating a supportive organizational climate and strengthening employee motivation to enhance job satisfaction and ultimately improve organizational commitment. Originality/Value: This study provides empirical evidence on the role of job satisfaction as a crucial mediator, strengthening the impact of organizational climate and motivation on commitment, particularly in the telecommunications industry within the specific regional context of Malang Raya. Practical/Policy implication: These results highlight the importance of organizations in creating a supportive organizational climate and strengthening employee motivation. By doing so, companies can enhance job satisfaction, which ultimately serves as a key driver of organizational commitment, reduced turnover, and maintained productivity. Keywords: Job Satisfaction; Organizational Climate; Organization Commitment; Work Motivation JEL Classification: M12, M54, J28